The Good or the Bad? Which Mutual Fund Managers Join Hedge Funds? - Deuskar, Prachi; Pollet, Joshua M.; Wang, Z. Jay; Zheng, Lu (Review of Financial Studies, 2011)
Does the mutual fund industry lose its best managers to hedge funds? We find that mutual funds are able to retain managers with good performance in the face of competition from a growing hedge fund industry. On the other hand, poor performers are more likely to leave the mutual fund industry. A small fraction of these poor performers find jobs with smaller and younger hedge fund companies, especially when the hedge fund industry is growing rapidly. Analogously, a small fraction of the better-performing mutual fund managers are retained by allowing them to manage a hedge fund side-by-side.